Perceived Barriers and Facilitators to Healthy Lifestyles and Weight Loss Among Adolescents with Overweight and Obesity: A Qualitative Study. (29th May 2020) - Cardel, Michelle; Lee, Alexandra; Dillard, Jackson; Dilip, Abhaya; Miller, Darci; Theis, Ryan; Bernier, Angelina; Thompson, Lindsay; Janicke, David; Szurek, Sarah
Abstract: Objectives: Obesity in adolescence has reached epidemic proportions around the world, with the prevalence of severe obesity increasing at least four-fold over the last 35 years. Provision of evidence-based treatment options that are tailored and relevant to the needs of adolescents is paramount, yet difficult to tailor because little is known regarding barriers and facilitators to adolescent weight loss. Thus, identification of barriers and facilitators to weight loss among adolescents with overweight/obesity (OW/OB) is needed. The objective of this qualitative study was to assess perceived barriers and facilitators to a healthy lifestyle and weight loss among adolescents with OW/OB. Methods: Using 2018–2019 data from eleven focus groups among adolescents aged 14–19 with OW/OB (n = 41; n = 11 boys and n = 30 girls), a moderated, semi-structured focus group guide was used to identify perceived barriers and facilitators to a healthy lifestyle and weight loss. Results: Adolescents reported time, access to healthful foods, food cravings, stress, and weight stigma/shaming as barriers to weight loss. Themes around internal and external psychosocial states (support, motivation) and behaviors including modeling, sports, and other physical activities were identified as both barriers and facilitators. Parents were recognized by teens as both helping and hindering weight loss, but overall teens felt their parents were more so facilitators than barriers, particularly as it related to modeling behaviors. Differences were noted by sex, among which girls reported experiencing weight struggles, whereas boys generally stated they did not struggle with weight, despite all participants meeting criterion for OW/OB. Conclusions: Adolescent boys and girls with OW/OB perceive their weight status differently and identify a variety of barriers and facilitators to a healthy lifestyle and weight loss. Tailoring adolescent weight management interventions to address these perceived barriers and facilitators, along with noted sex differences, has the potential to improve the quality and effectiveness of adolescent obesity interventions. Funding Sources: National Heart, Lung, and Blood Institute, National Institute of Health, WellCare Health Plans.